Flow field characteristics of Rayleigh streaming in a two-dimensional rectangular channel under the background physical field. (March 2023) - Yang, Yanfeng; Jiang, Genshan; Liu, Yuechao; Yang, Yang
Abstract: The purpose of this paper is to explore the flow field characteristics of Rayleigh streaming in a two-dimensional rectangular channel under the background physical field. Based on the Nyborg perturbation theory, the nonlinear acoustic streaming control equation of the coupled background physical field is derived. Furthermore, the finite element method is used to establish the numerical model of Rayleigh streaming in a two-dimensional rectangular channel under a background physical field. Finally, the Reynolds stress method is used to study the flow field characteristics of Rayleigh streaming in the uniform directional shear flow field and temperature gradient field. The reliability of the numerical method is verified by comparing it with the analytical solution of the classical Rayleigh streaming. The results show that the background flow field can restrain the Rayleigh streaming. When the average velocity of the background flow is greater than the particle velocity amplitude of the first-order sound field, the Rayleigh streaming is easily submerged by the background flow field. The streaming intensity decreases exponentially with the increase of the average velocity of the background flow. Moreover, Rayleigh streaming is very sensitive to the temperature gradient field. With the increase in a temperature gradient, the Rayleigh streaming vortex near the high-temperature region expands rapidly, and its streaming intensity increases exponentially. The conclusion of this paper provides a certain explanation for revealing the mechanism of flow heat transfer regulated by strong sound waves under the background physical field.